A Field Survey of Syrphid Species and Adult Densities on Annual Flowering Plants in the Northeastern United States. Issue 2 (17th February 2023) - Harris-Cypher, Alina; Roman, Caterina; Higgins, Genevieve; Scheufele, Susan; Legrand, Ana; Wallingford, Anna; Sideman, Rebecca Grube
Abstract: With the long-term goal of exploring the viability of conservation biological control of cabbage aphid Brevicoryne brassicae (L.) (Hemiptera: Aphididae) in the northeastern United States, adult syrphid flies (Diptera: Syrphidae) were observed on several species of annual insectary plants at farm sites in Connecticut, Massachusetts, and New Hampshire. Insectary plant species included alyssum, Lobularia maritima (L.) (Brassicales: Brassicaceae), buckwheat, Fagopyrum esculentum (Moench) (Caryophyllales: Polygonaceae), phacelia, Phacelia tanacetifolia (Bentham) (Boraginales: Hydrophyllaceae), calendula, Calendula officinalis (L.) (Asterales: Asteraceae) and ammi, Ammi majus (L.) (Apiales: Apiaceae). Among these insectary plants, alyssum had the longest bloom period and attracted the most syrphids. We identified 21 species of syrphid flies from insectary plants. The three most prevalent species collected were the aphidophagous Toxomerus marginatus (Say) (Diptera: Syrphidae) (70.1% of samples) and T. geminatus (Say) (Diptera: Syrphidae) (8.8% of samples), as well as the non-aphidophagous Syritta pipiens (L.) (Diptera: Syrphidae) (13.1% of samples). The benefits of including these insectary plant species as a companion to Brassica (L.) (Brassicales: Brassicaceae) cropping systems are discussed.